(untitled) (Medico Legal Update, 2019)
Background/Objectives: This study is a descriptive correlation study that investigated the relationship of smartphone addition, self-control, and learning flow among nursing students. Method/Statistical Analysis: The data was collected for 5 days from December 4 until December 8, 2017. In this study, 181 first-year students attending a nursing college in W city were convenience-sampled. Findings: In this study, the smartphone addiction score of the nursing students was 2.27 out of 4,self-control 3.84 out of 5, and learning flow2.91 out of 5. Analysis of the correlation among smartphone addiction, self-control, and learning flow showed that smartphone addiction and learning flow had negative correlation (r=-.357, p<.001); self-control and learning flow positive correlation (r=.408, p<.001); and self-control and smartphone addiction negative correlation (r=-.511, p<.001). Improvements/Applications: Therefore, development and application of manuals to prevent smartphone addition are required and various practical programs which can be evaluated and improve learning flow must be applied.